2014
DOI: 10.7155/jgaa.00324
|View full text |Cite
|
Sign up to set email alerts
|

Universal Point Sets for Drawing Planar Graphs with Circular Arcs

Abstract: We prove that there exists a set S of n points in the plane such that every n-vertex planar graph G admits a planar drawing in which every vertex of G is placed on a distinct point of S and every edge of G is drawn as a circular arc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…By Fáry's theorem, every planar graph can be drawn planarly with straight line segments for its edges, and therefore it can also be drawn with circular arcs. Indeed, there exist universal sets of n points such that every n-vertex planar graph can be drawn using those points for vertices and circular arcs for edges, something that is not true for straight-line drawing [2]. However, those arcs may not necessarily meet at equal angles.…”
Section: Lombardi Drawingmentioning
confidence: 99%
See 1 more Smart Citation
“…By Fáry's theorem, every planar graph can be drawn planarly with straight line segments for its edges, and therefore it can also be drawn with circular arcs. Indeed, there exist universal sets of n points such that every n-vertex planar graph can be drawn using those points for vertices and circular arcs for edges, something that is not true for straight-line drawing [2]. However, those arcs may not necessarily meet at equal angles.…”
Section: Lombardi Drawingmentioning
confidence: 99%
“…Let be the line through the three centers, assumed to exist by (2). Then because passes through each circle center, a reflection across is a symmetry of each circle and therefore of the whole configuration of three circles.…”
Section: Fig 17mentioning
confidence: 99%
“…If bends may be placed freely in the plane, then a construction of Everett et al using n points is universal for planar graphs [19]. Angelini et al constructed universal point sets of size n, lying on a parabolic path, for planar graphs where the edges are drawn as circular arcs [2]. If edges may consist of two smoothly connected semicircles, then n collinear points are universal for planar graphs [6,22].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Löffler and Tóth [24] showed that 6n − 10 points suffice for k = 1. Angelini et al [4] showed that n points suffice when we draw the edges as circular arcs.…”
Section: Theoremmentioning
confidence: 99%
“…See Figure 2. 4 to four points in convex position (on the left), then π(T ) has a crossing for all T ∈ T n . Otherwise, π(T ) is plane for at most one T ∈ T n (on the right).…”
Section: Large Universal Point Setsmentioning
confidence: 99%